ALIH AKSARA DAN ALIH BAHASA TEKS KITAB FADHILAH SYUHUR: MENERANGKAN BULAN RAMADHAN DAN KELEBIHAN IBADAH-IBADAH DI DALAMNYA DAN KELEBIHAN BULAN SYAWAL DISUSUN OLEH IMAM MAULANA ABDUL MANAF AMIN AL-KHATIB - Rahmawati, Nur; Nasution, Bakhtarudin; Nst., Muhammad Ismail (Jurnal Bahasa dan Sastra, 2017)
The purpose of this study: (a) presents about transliteration text â€œBook Fadhillah Syuhur: Describe the Month of Ramadhan and Excess Worships in it and Excess Month of Syawal Compiled by Imam Maulana Abdul Manaf Amin Al-Khatibâ€. (b) presents about translation text â€œBook Fadhillah Syuhur: Describe the Month of Ramadhan and Excess Worships in it and Excess Month of Syawal Compiled by Imam Maulana Abdul Manaf Amin Al-Khatibâ€. This study is a philology research. The object of this study is the text â€œBook Fadhillah Syuhur: Describibe the Month of Ramadhan and Excess Worships in it and Excess Month of Syawal Compiled by Imam Maulana Abdul Manaf Amin Al-Khatibâ€. The method that was used in this study suitable with stage of research. In this stage collect the data that is used library research and field research methods. In this stage of the description used descriptive method. In this stage of transliteration used transliteration method. In this stage translation used translation method. The finding of the study is avalaible of text about â€œBook Fadhillah Syuhur: Describe the Month of Ramadhan and Excess Worships in it and Excess Month of Syawal Compiled by Imam Maulana Abdul Manaf Amin Al-Khatibâ€ in Latin script and Indonesian language. In this text is found old Malay language diversity thatâ€™s retained to preserve the purity of vocabulary.Keywords: Philology, text, transliteration, translation.